The Influence of Product Orientation and Product Innovation on Competitive Advantage - Guntur Ade Saputra; Hapzi Ali; Yayan Hendayana (Greenation International Journal of Tourism and Management, 2024)
The research aims to determine the relationship between market orientation and competitive advantage, to determine the relationship between product innovation and competitive advantage. The method used in this research is a literature study, by collecting shared information related to the variables discussed. Namely related to product innovation, market orientation, and competitive advantage. This data and information was obtained through electronic media and then analyzed to determine deeper relationships between variables. The results of this research reveal that market orientation has a positive and significant effect on competitive advantage, this means that the better the company is in responding to market orientation, the company's competitive power and advantage will increase. Product innovation has a positive and significant effect on competitive advantage. This means that the more innovative a company is in developing new products or services, the higher the level of competitiveness of the company.